Corrado Gini, a pioneer in balanced sampling and inequality theory - Langel, Matti; Tillé, Yves (My University, 2011)
This paper attempts to make the link between two of Corrado Gini’s contributions to statistics: the famous inequality measure that bears his name and his work in the early days of balanced sampling. Some important notions of the history of sampling such as representativeness, randomness, and purposive selection are clarified before balanced sampling is introduced. The Gini index is described, as well as its estimation and variance estimation in the sampling framework. Finally, theoretical grounds and some simulations on real data show how some well used auxiliary information and balanced sampling can enhance the accuracy of the estimation of the Gini index.
Keywords: Gini; Inequality; Balanced sampling; Representativeness; Linearization; Purposive selection